Definitive radiotherapy for adenoid cystic carcinoma of main bronchus: a case report with 10-year follow-up - Nam, Sunghyun; Kim, Hyungsoon; Kim, Doyoon; Maeng, Jihoon; Shim, Hyo Sup; Kim, Dae Joon; Kim, EunYoung; Hong, Min Hee; Choi, Seo Hee; Cho, Jaeho (Frontiers in Oncology, 2026)
IntroductionTracheal adenoid cystic carcinoma (ACC) is a rare malignancy with a slow but relentless course. Surgical resection is the standard treatment, but in cases where surgery is not feasible, definitive radiotherapy serves as an alternative approach.Case descriptionWe report the case of a 55-year-old female patient diagnosed with unresectable ACC of the left main bronchus near the carina. Due to the high surgical risk of pneumonectomy with carinal reconstruction, the patient was treated with definitive intensity-modulated radiation therapy (IMRT) using a simultaneous integrated boost technique. A total dose of 69 Gy in 30 fractions was delivered. The patient tolerated the treatment well without significant acute or late complications. Follow-up imaging demonstrated a durable local response, with near-complete remission of the primary tumor. Ten years post-treatment, the patient remains free of local recurrence, with slow-progressing pulmonary metastases under surveillance.ConclusionThis case highlights the potential of definitive IMRT using a hypofractionated dose scheme in achieving long-term local control for unresectable tracheal ACC.